PRKCH regulates hematopoietic stem cell function and predicts poor prognosis in acute myeloid leukemia - Porter, Shaina N. (Exp Hematol, 2017)
Acute myeloid leukemia (AML) cells often co-opt normal hematopoietic stem cell (HSC) programs to drive neoplastic proliferation, and HSC-related gene expression signatures have been identified as biomarkers for poor prognosis in AML patients. We sought to identify new regulators of HSCs and AML cells from previously published HSC and leukemia stem cell (LSC) gene expression signatures. We identified PRKCH (Protein Kinase C eta) as a gene that is highly expressed in both mouse and human HSCs, as well as in LSCs from independent cohorts of AML patients. Prkch deletion in mice resulted in impaired HSC function. PRKCH was most highly expressed in undifferentiated (FAB M0) subtype AML, and high expression correlated with TP53 and RUNX1 mutations, high risk cytogenetic features, and poor overall survival. Prkch deletion in a Flt3-ITD/Runx1 mutant mouse AML model did not extend survival. Thus, PRKCH is necessary for normal HSC function, its expression predicts poor survival in AML patients, but it is not required for AML to develop.